Educational leadership in times of crisis - Grzegorz Mazurkiewicz (Risks, 2021)
The chain of crises experienced during the first two decades of the 21st century has changed life on Earth and concluded in a list of incredibly difficult challenges. It has become obvious that our traditional ways of acting do not work anymore. We need to search for new ideas and approaches. We want to believe in the potential of education. It manifests itself in different ways in beliefs, declarations, and actions. The work of education systems and institutions is a huge investment of commitment, time, and money. Governments, experts, workers, and service users have high hopes and enormous resources to keep education functioning. Everyone involved in designing solutions and carrying out tasks must understand how to respond to the global context and the challenges that humanity must deal with in order to survive. The environment and problems of public health, diversity and inequalities, technologies and social media, and the crisis of democracy affect the social reality and the world of education today. To be able to respond, both to challenges and to expectations, the human approach to leadership has to be transformed. The main problem for reformers is to define leadership again, using new assumptions and new intellectual tools. The research question worth asking is: what kind of educational leadership is needed? In this article, I propose a paradigm shift in thinking about educational leadership and a departure from the dominant classical paradigm. I propose a new model of educational leadership and adequate activities.
Keywords: 330; educational leadership; change; framework